Ergonomic intervention in the treatment of a patient with upper extremity and neck pain. - Fabrizio P (Physical Therapy, 2009)
BACKGROUND AND PURPOSE: Work-related musculoskeletal disorders are widespread among computer users and costly to the health care system. Workstation setup and worker postures contribute to upper-extremity and neck symptoms among computer users. Ergonomic interventions such as work risk analysis and workstation modifications can improve workers' symptoms. However, ergonomic interventions do not appear to be a common component of traditional physical therapy treatment. CASE DESCRIPTION: The patient was a 26-year-old woman with right upper-extremity and neck pain referred for physical therapy. A course of traditional physical therapy treatment was performed followed by an ergonomic intervention. OUTCOMES: Following 4 weeks of traditional physical therapy, the patient showed a 1.0-cm improvement in her resting pain level but no change in her pain level during exacerbations on the visual analog scale. An ergonomic intervention was performed following traditional physical therapy. At the conclusion of the full course of treatment (traditional physical therapy plus ergonomic intervention), resting pain level decreased by 4.6 cm and exacerbation pain level decreased by 3.2 cm. Improvements in Rapid Upper Limb Assessment and Workstyle scores also were realized. DISCUSSION: This case report demonstrates the importance of examining the work habits and work-related postures of a patient who complains of upper-extremity and neck pain that is exacerbated by work. Providing an ergonomic intervention in concert with traditional physical therapy may be the most beneficial course of treatment.